2017
DOI: 10.1111/cas.13268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MET inhibition on small‐cell lung cancer cells showing aberrant activation of the hepatocyte growth factor/MET pathway

Abstract: Small‐cell lung cancer (SCLC) accounts for approximately 15% of all lung cancers, and is characterized as extremely aggressive, often displaying rapid tumor growth and multiple organ metastases. In addition, the clinical outcome of SCLC patients is poor due to early relapse and acquired resistance to standard chemotherapy treatments. Hence, novel therapeutic strategies for the treatment of SCLC are urgently required. Accordingly, several molecular targeted therapies were evaluated in SCLC; however, they failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…To establish the LMC model, mouse scalps were sterilized with 70% ethanol, and tumor cells (2 Â 10 5 ) were injected into the leptomeningeal space (between the external occipital protuberance and first cervical vertebra) with a 27-gauge needle. 20 In the LMC model, tumor quantity was tracked in live mice by repeated noninvasive optical imaging of tumor-specific luciferase activity using the IVIS Lumina XR Imaging System (PerkinElmer, Alameda, CA), as previously described. 19,20 This study was performed in strict accordance with the recommendations of the Guide for the Care and Use of Laboratory Animals by the Ministry of Education, Culture, Sports, Science and Technology in Japan.…”
Section: Tumor Cell Inoculation In Severe Combined Immunodeficiency (mentioning
confidence: 99%
See 1 more Smart Citation
“…To establish the LMC model, mouse scalps were sterilized with 70% ethanol, and tumor cells (2 Â 10 5 ) were injected into the leptomeningeal space (between the external occipital protuberance and first cervical vertebra) with a 27-gauge needle. 20 In the LMC model, tumor quantity was tracked in live mice by repeated noninvasive optical imaging of tumor-specific luciferase activity using the IVIS Lumina XR Imaging System (PerkinElmer, Alameda, CA), as previously described. 19,20 This study was performed in strict accordance with the recommendations of the Guide for the Care and Use of Laboratory Animals by the Ministry of Education, Culture, Sports, Science and Technology in Japan.…”
Section: Tumor Cell Inoculation In Severe Combined Immunodeficiency (mentioning
confidence: 99%
“…20 In the LMC model, tumor quantity was tracked in live mice by repeated noninvasive optical imaging of tumor-specific luciferase activity using the IVIS Lumina XR Imaging System (PerkinElmer, Alameda, CA), as previously described. 19,20 This study was performed in strict accordance with the recommendations of the Guide for the Care and Use of Laboratory Animals by the Ministry of Education, Culture, Sports, Science and Technology in Japan. The protocol was approved by the Committee on the Ethics of Experimental Animals and the Advanced Science Research Center, Kanazawa University, Kanazawa, Japan (approval no.…”
Section: Tumor Cell Inoculation In Severe Combined Immunodeficiency (mentioning
confidence: 99%
“…PIM1, in turn, was shown to enhance the growth of lung adenocarcinoma by potentiating the c-MET signaling pathway [ 41 ] and the growth of prostate carcinoma [ 48 ] and triple-negative breast cancer [ 49 ] in cooperation with MYC. Importantly, some reports suggest the involvement of AKT, Wnt, MYC, and MET also in SCLC pathogenesis [ 50 53 ]. Hence, further studies are needed to elucidate whether overexpressed NEK2 and PIM1 induce similar promoting effects in SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, combination with chemotherapy was not assessed. In a more recent work, Taniguchi et al [87] also showed similar results, both in vitro and in vivo, with E7050 (golvatinib), a dual kinase inhibitor of MET and vascular endothelial growth factor receptor-2 (VEGFR-2), which is currently under clinical development [88]. Growth of SCLC cell lines expressing HGF and phosphorylated-MET (confirmed using Western blot and Enzyme-linked immunosorbent assay) was constrained after in vitro treatment with golvatinib.…”
Section: Met In Sclcmentioning
confidence: 99%